2007
DOI: 10.1007/s10571-007-9154-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolization of Porphyrinogenic Agents in Brain: Involvement of the Phase I Drug Metabolizing System. A Comparative Study in Liver and Kidney

Abstract: (1) We evaluated the involvement of brain mitochondrial and microsomal cytochrome P-450 in the metabolization of known porphyrinogenic agents, with the aim of improving the knowledge on the mechanism leading to porphyric neuropathy. We also compared the response in brain, liver and kidney. To this end, we determined mitochondrial and microsomal cytochrome P-450 levels and the activity of NADPH cytochrome P-450 reductase. (2) Animals were treated with known porphyrinogenic drugs such as volatile anaesthetics, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…This level of detail was not available for the majority of P450s. Finally, we assessed the presence of cytochrome P450 reductase (CRP) and ferredoxin reductase (FDXR) enzymes, which is a prerequisite for a functional enzymatic system (Bhagwat et al, 2000;Lavandera et al, 2007). Our results support the existence of active enzymes, as previously documented in human and rodent brain by measurement of microsomal monooxygenase activities and enzyme inhibition method (Miksys and Tyndale, 2009).…”
Section: Discussionsupporting
confidence: 81%
“…This level of detail was not available for the majority of P450s. Finally, we assessed the presence of cytochrome P450 reductase (CRP) and ferredoxin reductase (FDXR) enzymes, which is a prerequisite for a functional enzymatic system (Bhagwat et al, 2000;Lavandera et al, 2007). Our results support the existence of active enzymes, as previously documented in human and rodent brain by measurement of microsomal monooxygenase activities and enzyme inhibition method (Miksys and Tyndale, 2009).…”
Section: Discussionsupporting
confidence: 81%
“…The latter is considered a detoxification product, while N‐acetylbenzidine is oxidized to reactive intermediates that form DNA adducts (Choudhary, ), it will cause the organism to DNA damage, cell abnormal proliferation, tissue pathological change, even more to cancer. Both brain tissue impairment and neuron degeneration are some pathological lesions and may be due to an unexplored detoxification mechanism or to phagocytosis of cellular debris resulting from apoptosis when animal take some xenobiotic chemical such as synthetic azo dye (Ravindranath et al, ; Lavandera et al, ; Milbury and Kalt, ).…”
Section: Discussionmentioning
confidence: 99%
“…In developing countries, there has been an increasing concern as to the potential health effects of xenobiotics, including polycyclic aromatic hydrocarbons (PAHs), dioxin, pesticides, arylamine, and synthetic drugs, because these compounds have been associated with tissue dysfunction in a variety of species (Hill et al, ; Janosek et al, ; Scott et al, ). Although many valuable instruments can detect these xenobiotics in the environment, a traditional LC 50 offers scarce information regarding the actual impact on an organism at sublethal doses, such as cancer from benzidine exposure, infertility from 17α‐ethynylestradiol exposure, and brain neuropathy (Lotti, ; Lavandera et al, ; Vosges et al, ; Wang et al, ). The zebrafish is a popular animal model for the study of developmental toxicity because of its wide availability, transparent embryos, and well‐known genetic background (Hill et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…General anesthesia has been routinely used for surgical operations, and its safety has been assessed and established by clinical outcomes for sevoflurane (18), isoflurane (16), propofol (17) and dexmedetomidine (7). However, only a few studies have reported on the effects of anesthesia at the molecular level (2,15,19,25). Halothane (CF 3 CHBrCl), sevoflurane (CHF 2 -O-CHF-CF 3 ) and isoflurane (CHF 2 -O-CHCl-CF 3 ) are halogenated inhalation anesthetics that are metabolized by hepatic cytochrome P450, family 2, subfamily E, polypeptide 1 (CYP2E1) (13,14).…”
mentioning
confidence: 99%